Home oxygen use and 1-year outcome among preterm infants with bronchopulmonary dysplasia discharged from a Chinese regional NICU - Lin, Huijia; Chen, Xuefeng; Ge, Jiajing; Shi, Liping; Du, Lizhong; Ma, Xiaolu (Frontiers in Pediatrics, 2022)
Objective This study aims to compare the clinical characteristics and 1-year outcomes of preterm infants with bronchopulmonary dysplasia (BPD) who were discharged on supplemental oxygen or room air. Materials and Methods The preterm infants (born <32 weeks’ gestation, birth weight ≤1,250 g) diagnosed with BPD and admitted between January 2020 and December 2020 were enrolled. The clinical data during hospitalization were collected through the hospital’s electronic record system. The outcomes after discharge were acquired from the outpatient system and through telephonic interviews. Results Of the 87 preterm infants diagnosed with BPD, 81 infants survived until discharge. The 81 infants were divided into the home oxygen group (n = 29) and room air group (n = 52) according to supplemental oxygen or not at discharge. Infants in the home oxygen group were more likely to receive postnatal systemic steroids and higher ventilation settings at 36 weeks’ PMA. There was one patient in each group who died before 1 year corrected age, respectively. All the infants had successfully weaned off oxygen eventually during the first year. The median duration of home oxygen therapy was 25 (7,42) days. Readmission occurred in 49 (64.5%) infants. Readmissions for infants with home oxygen were more often related to respiratory disease. In addition, wheezing disorders and home inhalation occurred more frequently in the home oxygen group (p = 0.022, p = 0.004). Although the incidence of underweight at 1 year corrected age was higher in the room air group (10.0 vs. 3.8%), there was no significant difference (p = 0.620). The rate of neurodevelopmental impairment was similar between these two groups (26.0 vs. 30.8%, p = 0.659). Conclusions It was the first study focused on preterm infants with BPD receiving home oxygen in China. Infants with home oxygen were more likely to have respiratory problems after discharge from NICU. Home oxygen use was not associated with more readmission for infants with BPD, and no difference was found in neurodevelopmental impairment and growth outcome.